KUALITAS PELAYANAN APLIKASI MOBILE PAKDE SEMAR HEBAT! DI BADAN PENDAPATAN DAERAH KOTA SEMARANG - Neisya Rahma Isyak, Siti; Subowo, Ari; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research focuses on the problems of local tax services through the Pakde Semar Hebat! mobile application. These problems include several features in the application that cannot be fully accessed on iOS-based mobile phones, the slow service process, the low number of application users, people who still often come to the service office rather than doing services through the application, and a workload exceeding the number of employees at the Regional Revenue Agency of Semarang City. The purpose of this study to analyze the service quality of Pakde Semar Hebat! mobile application at Semarang City Regional Revenue Agency, and to identify factors related to the service quality of Pakde Semar Hebat! mobile application at Semarang City Regional Revenue Agency. This research uses a qualitative method with a descriptive type with an informant selection technique, namely purposive sampling and to test the validity of the data using source triangulation and technical triangulation. The data collection techniques used were interviews, observation, and documentation. The theory used in this research is the five-dimensional theory according to Parasuraman which includes tangibles, reliability, responsiveness, assurance, and empathy and the theory of factors related to service quality according to Moenir which includes awareness factors, regulatory factors, organizational factors, ability and skill factors. The results showed that the service quality of Pakde Semar Hebat! mobile application at Semarang City Regional Revenue Agency is quite optimal, but some aspects still need to be improved.